Increased Cancer Screening for Low-income Adults Under the Affordable Care Act Medicaid Expansion. Issue 11 (November 2018) - Hendryx, Michael; Luo, Juhua
Abstract : Background: We tested whether Medicaid expansion under the Affordable care Act was associated with increased screening for cervical, breast, and colorectal cancer among low-income adults. Methods: We analyzed Behavioral Risk Factor Surveillance System data, identifying 2012 as preexpansion and 2016 as postexpansion (2014 was treated as a wash-out, and 2013 and 2015 had missing screening data from most states). States (including District of Columbia) either expanded Medicaid in 2014 (n=28) or not (n=18); five states that expanded after 2014 were excluded. Participants included low-income adults aged 18–64 without dependent children. A difference-in-difference approach tested whether expansion was significantly associated with screening, controlling for time, state effects, age, sex, race/ethnicity, education, and urban/rural population. For comparison, we also conducted analyses among the low-income Medicare (aged 65 and above) population, and a higher income population. Results: There was a significant expansion effect for women aged 18–64 for cervical cancer screening (N=29, 059; odds ratio, 1.04; 95% confidence interval, 1.01–1.08), and for adults 50–64 for colorectal cancer screening (N=32, 290; odds ratio, 1.12; 95% confidence interval, 1.03–1.22). Effects for mammography for women aged 40–64, or aged 50–64, were not significant. As expected, there were no significant improvements associated with expansion among the Medicare population, or among a population ineligible due to higher income. Conclusions: Medicaid expansion under the Affordable Care Act was associated with increased screening for cervical and colorectal cancer for low-income adults. It will be important to monitor possible adverse cancer outcomes in nonexpansion states among vulnerable populations over time.